Callus distraction with external fixator for the treatment of congenital brachymetatarsia of the fourth ray. Issue 6 (August 2020) - Fuiano, Mario; Mosca, Massimiliano; Caravelli, Silvio; Di Liddo, Michele; Grassi, Alberto; Majumdar, Aditi; Massimi, Simone; Catanese, Giuseppe; Zaffagnini, Stefano
Highlights: Brachymetatarsia is a rare abnormality of the foot which occurs most frequently in the first and fourth metatarsals. The most common surgical interventions include one-stage metatarsal lengthening and callus distraction gradual metatarsal lengthening via an external fixator. Conservative treatment should always be the first approach. "Callus distraction" is generally more indicated in brachymetatarsia cases when a larger correction is needed. Particular attention should be given to treating patients with shortening >20 mm. Abstract: Background: Brachymetatarsia is a rare abnormality of the foot which occurs most frequently in the first and fourth metatarsals. The aim of this study was to evaluate the efficacy of gradual metatarsal lengthening by external fixator for treatment of brachymetatarsia of the fourth ray. The hypothesis was that with external fixation it would be possible to achieve the desired length of the metatarsal with a low rate of complications. Secondarily, in cases requiring a greater amount of correction, it was hypothesized that an opportune rate of bone consolidation would be achievable using a traditional oscillating saw without predrilling or use of a cold osteotome. Methods: Between 2013 and 2016, 12 eligible patients and 13 feet underwent gradual metatarsal lengthening by an external fixator (MiniRail System M103, Orthofix) due to brachymetatarsia of the fourth ray. Mean age at surgery was 24.5 ± 5.3 years (range 19–36), with mean follow-up of 22.3 ± 8.3 months. Clinical evaluation was performed with the AOFAS lesser metatarsophalangeal-interphalangeal (MTP-IP) score. Radiographic assessment was performed on follow-up using non-weightbearing dorsoplantar foot radiographs. Results: The mean AOFAS lesser MTP-IP score improved from a preoperative score of 76.6 ± 7.1 points (range 62–85 points) to a postoperative score of 90.3 ± 3.0 points (range 86–95 points). The average amount of lengthening was 16.8 ± 3.9 mm (range 8–22 mm). Mean shortening, final lengthening, Healing Index, period of treatment, and complications are also reported. The operative technique is described. Conclusions: Gradual metatarsal lengthening with external fixator is an effective treatment for brachymetatarsia and can restore forefoot anatomy with good clinical outcomes, a low rate of morbidity and complications in selected cases. Particular attention should be given when treating patients with shortening >20 mm.